The effects of dietary Agaricus bisporus powder on growth performance, haematological indices, and serum immune response in beluga (Huso huso) juvenile - Afshin Aminzadeh; Valiollah Jafari; Seyed Hossein Hoseinifar (Frontiers in Marine Science)
IntroductionThe present study investigates the effects of mushroom powder (MP) on growth parameters, haematological indices, innate immune response, and serum biochemical indices in beluga (Huso huso) juveniles.MethodsA total of 120 fish (45 ± 0.5 g) were stocked with 10 fish in each 300-L tank. Experimental diets were prepared by inclusion of 0, 0.5, 1.0, and 2.0% MP. At the end of the feeding trial haemato-immunological parameters as well growth performance were measured.ResultsThe growth parameters results revealed that body weight, specific growth rate (SGR), and body length increased significantly in the fish fed diets containing 1% and 2% MP (P<0.05). Haematological indices results indicated that none of the experimental diets showed significant effects on red blood cell count (RBC), hemoglobin, mean corpuscular volume (MCV), mean cell hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) (P >0.05). However, the haematocrit increased significantly in the fish fed diets containing 1% MP compared to the control (P<0.05). White blood cell count (WBC) in the fish fed 2% MP was significantly higher than that in the fish fed 0% and 0.5% MP (P<0.05). Furthermore, MP treatments caused no significant change in the activity of complement C3 (P >0.05), while C4 activity increased significantly in the fish fed 2% MP (P<0.05). Total immunoglobulin in 1% MP had no significant difference when compared with control (P >0.05). Albumin level was significantly higher in fish fed 2% MP compared to control (P<0.05).DiscussionIn conclusion, MP (2%) can be considered to improve growth parameters and immune indices in beluga juveniles.